Detection of Phenolic Compounds in Various Point Sources in Aba River, Nigeria - Okwunodulu, Felicia Uchechukwu; Imo, David Ugwo (Jurnal Bio-Geo Material Dan Energi, 2026)
Water is very important for all living organisms on earth and most of these waters in Nigeria are being polluted on a daily basis including surface water due to too much unregulated anthropogenic activities. Phenolic compounds are among the chemicals of major concern because of their persistent tendency in the environment and toxicity. The aim of this work is to detect phenolic compounds in various point sources in Aba river using GC/MS analysis. Based on the results, the water is acidic, pH ranged from 5.48 - 5.90. Thirty-two phenolic compounds were detected in all the samples although three same compounds were detected in samples 1 and 2, in other words twenty-nine different phenolic compounds were detected with their percentages ranging from 0.131-37.266. Some of these phenolic compounds are emanated from agricultural practices, effluents from pharmaceuticals, personal care products, foods, chemical, agro-chemicals industries and are very toxic therefore, this calls for a concern since their levels were above both USEPA and European Union standards